2003
DOI: 10.1176/appi.ajp.160.9.1699
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dopamine Transporter Loss in the Orbitofrontal and Dorsolateral Prefrontal Cortices With Methamphetamine-Related Psychiatric Symptoms

Abstract: Chronic methamphetamine use may cause dopamine transporter reduction in the orbitofrontal cortex, dorsolateral prefrontal cortex, and amygdala in the brain. Psychiatric symptoms in methamphetamine users may be attributable to the decrease in dopamine transporter density in the orbitofrontal cortex and the dorsolateral prefrontal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
157
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(170 citation statements)
references
References 10 publications
11
157
0
1
Order By: Relevance
“…Methamphetamine and cocaine abusers show altered function in prefrontal and striatal dopaminergic circuits (Baxter et al, 1988;Chang et al, 2005;Sekine et al, 2003;Volkow et al, 2001a;2001b). Dopaminergic systems in the striatum and prefrontal cortex are also thought to be involved in attention, working memory and impulse control (Arnsten and Li, 2005;Cardinal et al, 2004;Evenden, 1999;Paulus et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methamphetamine and cocaine abusers show altered function in prefrontal and striatal dopaminergic circuits (Baxter et al, 1988;Chang et al, 2005;Sekine et al, 2003;Volkow et al, 2001a;2001b). Dopaminergic systems in the striatum and prefrontal cortex are also thought to be involved in attention, working memory and impulse control (Arnsten and Li, 2005;Cardinal et al, 2004;Evenden, 1999;Paulus et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine (METH), a compound structurally similar to amphetamine also affects the dopamine system, e.g. it leads to downregulation of striatal D2 dopamine receptors (Chang and Haning, 2006) and dopamine transporters in the striatum (McCann et al, 1998), orbitofrontal cortex, and dorsolateral prefrontal cortex (Sekine et al, 2003). Although cocaine and amphetamines have different pharmacodynamic properties, both substances reduce the availability of D2 receptors, which is thought to alter the individual's ability to perform reward-related behaviors (Volkow et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…has also revealed a reduction of the DAT in MA abusers and in baboons after MA injection [63][64][65][66] .…”
Section: [ 11 C] Win 35428mentioning
confidence: 94%
“…In the PET study with [ 18 F] FCT in the cocaine self-administration model with monkeys, the laterality of DAT function was changed even before enough cocaine was consumed to produce significant overall changes in receptor and transporter availability [58] . has also revealed a reduction of the DAT in MA abusers and in baboons after MA injection [63][64][65][66] .Methylphenidate ( d-threo-MP to the DAT, suggesting that it is a useful PET tracer for imaging presynaptic dopaminergic neurons [67] . A PET imaging study using pretreatment with MP showed a marked decrease of [ 11 C] d-threo-MP binding in the human brain [68] .…”
mentioning
confidence: 99%
“…In view of research which has demonstrated ecstasy-related degradation in regions of the PFC (Sekine et al 2003) and hippocampus (Thompson et al 2004), and research showing ecstasy-related impairment within the working memory system Montgomery et al 2005b;Wareing et al 2004), it is not surprising that ecstasy users have poorer memory for associative information relative to nonusers (Croft et al 2001b;Gouzoulis-Mayfrank et al 2003;Montgomery et al 2005a). Using a paired associated learning (PAL) task, Croft et al (2001b) asked a sample of ecstasy and cannabis users, cannabis only users and drug naive counterparts to learn associations between six spatially defined stimulus pairs ("spatial") or six colour pairings ("non-spatial").…”
mentioning
confidence: 99%